Development and Validation of Reversed-phase High-performance Liquid Chromatography Method for the Simultaneous Estimation of Benzoyl Peroxide and Resveratrol: Development and Validation of Reversed-phase High-performance Liquid Chromatography Method for the Simultaneous Estimation of Benzoyl Peroxide and Resveratrol - Kamra, Manju (International Journal of Pharmaceutical & Biological Archive, 2018)
A new, reliable, and sensitive reversed-phase high-performance liquid chromatography method has been developed and validated for simultaneous assay of benzoyl peroxide (BPO) and resveratrol. An isocratic separation of BPO and resveratrol was achieved on C18, 250 mm × 4.6 mm I.d., 5 μm particle size columns with a flow rate of 1.2 ml/min and using a UV detector to monitor the elute at 245 nm. The mobile phase consisted of an ammonium acetate (pH 4) and ethanol. Response was a linear function of drug concentration in the range of 10–100 mg/mL range with an R2 of 0.993 for BPO and 10–100 μg/mL range with an R2 of 0.995 for resveratrol, accuracy with percent relative standard deviation of 100.65 ± 0.23 (benzoic peroxide) and 100.48 ± 0.45 (resveratrol) and with a limit of detection and quantification for BPO and resveratrol, respectively. The result of analysis has been validated statistically and by recovery study. The accuracy ranged between 99.65 and 101.91%. The method was found to be precise, reproducible, and rapid.